2022
DOI: 10.1111/tbed.14505
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and comparison of hemagglutination inhibition and indirect immunofluorescence tests for the detection of antibodies against duck Tembusu virus

Abstract: Currently, duck Tembusu virus (DTMUV), an emerging avian pathogenic flavivirus, is widely spread and becomes endemic in duck populations in Asia, causing significant economic losses in the duck producing industry. To early detection and control of DTMUV, the well-validated diagnostic tests for efficient detection of DTMUV infection in ducks are needed. In this study, we validated and compared hemagglutination inhibition (HI) and indirect immunofluorescence (IFA) tests for identifying antibodies against DTMUV i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
(71 reference statements)
0
0
0
Order By: Relevance
“…By validating and comparing the hemagglutination inhibition (HI) and indirect immunofluorescence (IFA) methods for detecting DTMUV antibodies in duck serum, it was found that both methods have high sensitivity (100%) and specificity (>87%) and show over 90% agreement with the serum neutralization (SN) test results. Compared to the IFA test, the HI method demonstrated higher specificity and a stronger correlation with the SN test [105].…”
Section: Diagnostic Methodsmentioning
confidence: 91%
“…By validating and comparing the hemagglutination inhibition (HI) and indirect immunofluorescence (IFA) methods for detecting DTMUV antibodies in duck serum, it was found that both methods have high sensitivity (100%) and specificity (>87%) and show over 90% agreement with the serum neutralization (SN) test results. Compared to the IFA test, the HI method demonstrated higher specificity and a stronger correlation with the SN test [105].…”
Section: Diagnostic Methodsmentioning
confidence: 91%